The Lingvodydactic Model of the Assessment of Writing Competence in a Foreign Language - Ignatjeva, Larisa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The setting of humanistic concept of education demands the revision of the whole lingvodidactic system of foreign language learning. On the modern stage of the development of pedagogy that allows to put theory into the practice of teaching and assessment of students’ achievements the search for educational models is especially actual. The most important area of the realization of humanistic approach is school education as the development of students’ personality takes place particularly at school age. The article analyses a lingvodydactic model of the competence assessment in writing. The main aim of the working out of this model is to overcome the contradiction between a formal way of assessment which is objective and the necessity of the creation of the conditions for students’ full personal self-expression. This system is being approbated in the Russian language learning as a foreign language in Latvian schools.